Assessment of the sardine (Sardina pilchardus Walbaum, 1792) fishery in the eastern Mediterranean basin (North Aegean Sea) - ANTONAKAKIS, K.; GIANNOULAKI, M.; MACHIAS, A.; SOMARAKIS, S.; SANCHEZ, S.; IBAIBARRIAGA, L.; URIARTE, A. (Mediterranean Marine Science, 2011)
The aim of this study was to describe the biometric characteristics of the European sardine (Sardina pilchardus) catches and assess the current status of sardine stock in North Aegean Sea based on population characteristics and abundance trends. The stock was dominated by age groups 1 and 2, not exceeding age group 4. The sardine stock in this area was assessed through an Integrated Catch-at-Age model which implements a separable Virtual Population Analysis on catch at age data with weighted tuning indices. Sardine landings data derived from the commercial purse seine fishery over the period 2000-2008 were combined with the age structure of the stock as resulted from fisheries independent acoustic surveys. Sensitivity analysis of the impact of natural mortality values on stock assessment results was applied. Additionally forecast of the sardine population parameters and catches under different exploitation scenarios was implemented in a medium term basis. Results indicated that the North Aegean Sea sardine stock is considered fully exploited with the fishery operating close but over the empirical exploitation level for sustainability. Finally, the status of the sardine stock in N. Aegean Sea is discussed in relation to the sardine stocks from the western and the central Mediterranean basin.